PET Recycling by Alcoholysis Using a New Heterogeneous Catalyst: Study and its Use in Polyurethane Adhesives Preparation - Scremin, Duanne M.; Miyazaki, Danilo Y.; Lunelli, Carlos E.; Silva, Simone A.; Zawadzki, Sônia F. (Macromolecular symposia., 2019)
One of the most used plastics in the world is poly(ethylene terephthalate), PET, which is on the top of the list of recyclable polymers. In this work, it was studied the chemical recycling of PET by the alcoholysis reaction using diethylene glycol (DEG) and sodium metasilicate (NaMs) as catalyst. This catalyst was not used before for this kind of reaction and showed an activity as good as the most used compound (zinc acetate). The PET‐polyol was produced with the reaction conditions that showed the higher weight yield and the final product was used in polyurethane (PU) adhesives compositions. The PUs were obtained using PET‐polyol, tolylene diisocyanate (10, 20 or 30% NCOfree) and DEG as chain extender or glycerin (GLY) as crosslinker. The adhesives were poured into Pinus taeda wood and the speciments were taken into mechanical properties evaluation accordingly to ASTM D 2339‐98. The results indicated that the PU adhesives 10% NCOfree with DEG were able to support the highest shear stress force applied (7.5 Mpa).